Lockdowns for community containment of COVID-19: Present challenges in the absence of interim guidelines - Md Dilshad Manzar; Seithikurippu R Pandi-Perumal; Ahmed S Bahammam (Wolters Kluwer Medknow Publications, 2020)
The implementation of lockdown as a method of community containment is complex and affects the several aspects of daily living. There is an urgent need for the development of guidelines for lockdowns as community containment methods to prevent pandemics. This opinion presents five broad areas of concern affecting community-containment strategies. This viewpoint may help in the development of an interim guide for the adequate implementation of community containment strategies. The presence of the COVID-19 pandemic, which now influences nearly every country, emphasizes the urgency of adopting meaningful and doable-threat reduction strategies that will fulfill the need of the local populations.